2016
DOI: 10.1080/02640414.2016.1201212
|View full text |Cite
|
Sign up to set email alerts
|

Morning–evening difference of team-handball-related short-term maximal physical performances in female team handball players

Abstract: This study investigated the two different time-of-day effect on team-handball-related short-term maximal physical performances. At two different time-of-day, fifteen young female team handball players performed different physical tests: HandGrip (HG) test, Ball-Throwing Velocity (BTV) test, Modified Agility T-test (MAT) and Repeated Shuttle-Sprint and Jump Ability (RSSJA) test. Rating of perceived exertion (RPE) scale was determined following the termination of the last test. Measurements were performed at two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
22
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 44 publications
9
22
1
6
Order By: Relevance
“…Previous studies ( Chtourou and Souissi, 2012 ; Mhenni et al, 2017 ; West et al, 2014 ; Zarrouk et al, 2012 ) confirmed maximal shortterm performances depend on the time of day completed with morning nadirs and afternoon peaks. For example, high-intensity short duration performance is usually higher in the afternoon (16:00-20:00 h) compared to the morning (6:00-10:00 h) ( Zarrouk et al, 2012 ).…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…Previous studies ( Chtourou and Souissi, 2012 ; Mhenni et al, 2017 ; West et al, 2014 ; Zarrouk et al, 2012 ) confirmed maximal shortterm performances depend on the time of day completed with morning nadirs and afternoon peaks. For example, high-intensity short duration performance is usually higher in the afternoon (16:00-20:00 h) compared to the morning (6:00-10:00 h) ( Zarrouk et al, 2012 ).…”
Section: Introductionmentioning
confidence: 70%
“…This variation in muscle power, strength and sprint ability ranges from 3 to 21% depending on the muscle group and athlete sample investigated ( Chtourou and Souissi, 2012 ). Specifically in handball players, Mhenni et al (2017) reported maximal handgrip strength of the dominant hand (19.4%, effect size (ES) = 0.73), ball throwing velocity (5.4%, ES = 0.50) and change-of-direction speed (12.1%, ES = 1.59) were higher in the evening compared to the morning. However, in addition to strength, throwing and change-of-direction attributes, handball players also undergo extensive sprinting activity with and without a ball over 5-20 m as well as they need to respond to extensive jumping demands during match-play ( Wagner et al, 2014 ).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations